Management of fracture risk in CKD-traditional and novel approaches - Haarhaus Mathias; Aaltonen Louise; Cejka Daniel; Cozzolino Mario; de Jong Renate T; D'Haese Patrick; Evenepoel Pieter; Lafage-Proust Marie-Hélène; Mazzaferro Sandro; McCloskey Eugene; Salam Syazrah; Jørgensen Hanne Skou; et al. (Oxford University Press, 2025)
The coexistence of osteoporosis and chronic kidney disease (CKD) is an evolving healthcare challenge in the face of increasingly aging populations. Globally, accelerating fracture incidence causes disability, impaired quality of life and increased mortality. Consequently, several novel diagnostic and therapeutic tools have been introduced for treatment and prevention of fragility fractures. Despite an especially high fracture risk in CKD, these patients are commonly excluded from interventional trials and clinical guidelines. While management of fracture risk in CKD has been discussed in recent opinion-based reviews and consensus papers in the nephrology literature, many patients with CKD stages 3–5D and osteoporosis are still underdiagnosed and untreated. The current review addresses this potential treatment nihilism by discussing established and novel approaches to diagnosis and prevention of fracture risk in patients with CKD stages 3–5D. Skeletal disorders are common in CKD. A wide variety of underlying pathophysiological processes have been identified, including premature aging, chronic wasting, and disturbances in vitamin D and mineral metabolism, which may impact bone fragility beyond established osteoporosis. We discuss current and emerging concepts of CKD–mineral and bone disorders (CKD-MBD) and integrate management of osteoporosis in CKD with current recommendations for management of CKD-MBD. While many diagnostic and therapeutic approaches to osteoporosis can be applied to patients with CKD, some limitations and caveats need to be considered. Consequently, clinical trials are needed that specifically study fracture prevention strategies in patients with CKD stages 3–5D.